Towards the first linkage map of the Didymella rabiei genome. - Lichtenzveig, Judith; Winter, P.; Abbo, S.; Shtienberg, D.; Kaiser, W.; Kahl, G. (Springer, 2002)
A genetic map was developed for the ascomycete Didymella rabiei (Kovachevski) v. Arx (anamorph: Ascochyta rabiei Pass. Labr.), the causal agent of Ascochyta blight in chickpea (Cicer arietinum L.). The map was generated with 77 F1 progeny derived from crossing an isolate from the U.S.A. and an isolate from Syria. A total of 232 DAF (DNA AmplificationFingerprinting) primers and 37 STMS (Sequence-Tagged Microsatellite Site) primer pairs were tested for polymorphism between the parental isolates; 50 markers were mapped, 36 DAFs and 14 STMSs. These markers cover 261.4cM in ten linkage groups. Nineteen markers remained unlinked. Significant deviation from the expected 1:1 segregation ratios was observed for only two markers (Prob. of x2 <0.05). The implications of our results on ploidy level of the asexual spores are discussed.